Implementation of Digital Signature on Banking - Hamdi, Nurul; Junidar, Junidar (Ubudiyah Indonesia University, 2016)
One of the advantages of doing business in the internet world is can he do trade transactions where and at any time, without the presence of physical or face to face directly. In terms of profit in its own problems arose, mainly related to authentication. Bagaimanapenj ual can rest assured that the purchased product is the correct person or how the seller know that the credit card used the buyer is legitimate credit card hers. The example above is one of the problems in the internet world you can finish with a digital signature. There are still many more problems in the internet that can be solved with the use of a digital signature or digital signature misalnyadi the field of ecommerce, internet banking and more.Keyword:D igital Signatures, internet, e-commerce